"The safety of sodium reduction in the food supply: A cross-discipline balancing act"—Workshop proceedings. Issue 10 (3rd July 2018) - Taylor, Christine; Doyle, Michael; Webb, Densie
ABSTRACT: This workshop, jointly presented by the ILSI North America Technical Committees on Food Microbiology and Sodium, aimed to provide greater knowledge and appreciation of the opportunities and challenges facing the food industry in answering the public health community's call to reduce sodium levels in the food supply. One major challenge is finding effective substitutes for the various antimicrobial and functional roles that sodium plays across different food categories. Sodium plays a critical role in retarding the growth of pathogens and food spoilage bacteria. Moreover, taste is an important factor for consumers when they choose food products, and the flavor changes that occur when salt is reduced or replaced must be considered and ingredients and processes adjusted accordingly. The workshop provided a platform for a multidisciplinary discussion among the microbiology, food science, nutrition, and public health communities to share progress and propose solutions, including the formation of public-private partnerships, to develop coordinated and comprehensive strategies. This paper provides an overview of the issues raised, rather than a specific summary of workshop discussions. The Food and Drug Administration's Draft Guidance for Industry on voluntary sodium reduction and the 2015 US Dietary Guidelines for Americans were released subsequent to the workshop and are also discussed.